Impact of partial-volume effect correction on the predictive and prognostic value of baseline 18F-FDG PET images in esophageal cancer - Hatt, Mathieu (Society of Nuclear Medicine, 2012)
The objectives of this study were to investigate the clinical impact of partial volume effects (PVE) correction on the predictive and prognostic value of metabolically active tumor volume (MATV) measurements on 18F-FDG PET baseline scan for therapy response and overall survival in esophageal cancer patients. METHODS: 50 patients with esophageal cancer treated with concomitant radio-chemotherapy between 2004 and 2008 were retrospectively considered. PET baseline scans were corrected for PVE with iterative deconvolution incorporating wavelet denoising. MATV delineation on both original and corrected images was carried out using the automatic Fuzzy Locally Adaptive Bayesian (FLAB) methodology. Several parameters were extracted considering the original and corrected images: maximum and peak SUV, mean SUV, MATV and TLG (TLG=MATV×mean SUV). The predictive value of each parameter with or without correction was investigated using Kruskal-Wallis tests and the prognostic value with Kaplan-Meier curves. RESULTS: Whereas PVE correction had significant quantitative impact on the absolute values of the investigated parameters, their clinical value within the clinical context of interest was not significantly modified. This was observed for both overall survival and response to therapy. The hierarchy between parameters was the same before and after correction. SUV measurements (max, peak, mean) had non-significant (p>0.05) predictive or prognostic value, whereas functional tumor related measurements (MATV, TLG) were significant (p<0.002) predictors of response and independent prognostic factors. CONCLUSIONS: PVE correction does not improve the predictive and prognostic value of baseline PET image derived parameters in esophageal cancer patients.